Evaluasi Pengukuran Kinerja Keuangan Pada PT Indofood Sukses Makmur Menggunakan Rasio Arus Kas - Febryanti Febryanti Febryanti; Syntha Noviyana Noviyana (Ridwan Institute, 2022)
The purpose of this study was to analyze the financial performance as measured by the cash flow ratio at PT. Indofood Sukses Makmur Tbk. 2018-2020 period. This study uses the following cash flow ratio analysis methods: operating cash flow ratio (AKO), fund flow coverage ratio (CAD), cash to interest coverage ratio (CKB), cash to current debt coverage ratio (CKHL), capital expenditure ratio (PM), the ratio of total debt (TH). The type of data used in this research is quantitative data. Sources of data used are secondary data, namely the Statement of Financial Position, Income Statement and Cash Flow Statement at PT. Indofood Sukses Makmur Tbk period 2018-2020. The data collection technique is a documentation study, namely through the page on the Indonesia Stock Exchange. The results of the study note that the financial performance of PT. Indofood Sukses Makmur Tbk for the 2018-2020 period shows that there are three cash flow ratios whose values ​​are still below the applicable standard criteria because the company has not been able to meet current obligations and long-term debt on time but the company can cover interest costs, capital expenditures, and is able to pay taxes. of the cash flow generated by the company.